Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.